Diagnostic algorithm in men suspected with nonobstructive azoospermia - Mahdi Bazzi; Matthew Chabot; Amarnath Rambhatla; Eric Chung (Asian Journal of Andrology)
This review focuses on the diagnostic algorithm for nonobstructive azoospermia (NOA), a significant male factor contributing to infertility. NOA, characterized by the absence of sperm in the ejaculate, requires a systematic diagnostic approach to identify reversible conditions, genetic factors, and prognosis for achieving pregnancy. The diagnostic pathway involves semen analysis and a comprehensive evaluation for hormonal deficiencies, anatomical abnormalities, and genetic factors. The importance of medical history, physical examination, endocrine evaluation, imaging, and genetic testing is emphasized. This review highlights the significance of differentiating NOA from obstructive azoospermia (OA) and outlines key considerations for effective management, including surgical sperm retrieval and assisted reproductive techniques. Testicular biopsy is discussed as a definitive method to distinguish obstructive cases from nonobstructive cases, providing valuable prognostic information. Overall, a thorough and systematic diagnostic approach is essential for the effective management of men suspected with NOA, offering insights into potential treatment options and reproductive outcomes.